2008
DOI: 10.1073/pnas.0801925105
|View full text |Cite
|
Sign up to set email alerts
|

Resistance, resilience, and redundancy in microbial communities

Abstract: Although it is generally accepted that plant community composition is key for predicting rates of ecosystem processes in the face of global change, microbial community composition is often ignored in ecosystem modeling. To address this issue, we review recent experiments and assess whether microbial community composition is resistant, resilient, or functionally redundant in response to four different disturbances. We find that the composition of most microbial groups is sensitive and not immediately resilient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
1,646
9
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,323 publications
(1,745 citation statements)
references
References 58 publications
78
1,646
9
12
Order By: Relevance
“…Dormancy has the potential to explain numerous ecological patterns observed in microbial systems over the past decade, including repeated seasonal succession (6), the rare microbial biosphere (22), and the apparent resilience to disturbance of microbially mediated processes (48). In addition, the dormancydriven decoupling of active and total composition observed in our study raises the question of whether we must consider the use of rRNA-based approaches to link microbial community structure and function.…”
Section: Resultsmentioning
confidence: 74%
“…Dormancy has the potential to explain numerous ecological patterns observed in microbial systems over the past decade, including repeated seasonal succession (6), the rare microbial biosphere (22), and the apparent resilience to disturbance of microbially mediated processes (48). In addition, the dormancydriven decoupling of active and total composition observed in our study raises the question of whether we must consider the use of rRNA-based approaches to link microbial community structure and function.…”
Section: Resultsmentioning
confidence: 74%
“…Although other groups (particularly gram-negative bacteria) may also have contributed to differences in the direction of priming between litter treatments, only gram-positive bacteria showed a consistent response to temperature. A meta-analysis by Allison and Martiny (2008) found that the majority (80%) of soil-warming experiments showed changes in microbial community structure, and many studies (although not all) show increases in gram-positive bacteria (Zogg et al, 1997;Rinnan et al, 2007;Frey et al, 2008;Feng and Simpson, 2009;Schindlbacher et al, 2011;Ziegler et al, 2013;Wei et al, 2014;Xiong et al, 2014); a microbial group associated with soil-C decomposition in this study and often associated with mineral C decomposition and low substrate availability (Fierer et al, 2003;Kramer and Gleixner, 2008). The results from our study suggest that this microbial group may potentially mediate the response of soil-C mineralization and priming in a warming climate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role microbial community structure and function plays in soil and litter turnover, and its response to elevated temperatures and N availability, is less understood. The concept of a functional redundancy of microbial communities, where under the right environmental circumstances the same functions and processes can be performed regardless of the microbial community present in the soil, has recently been challenged (Allison and Martiny, 2008;Strickland et al, 2009), and changes to microbial community structure have been linked to a wide range of ecosystem processes (Wardle et al, 2004;Balser and Firestone, 2005;Lau and Lennon, 2012;. For example, distinct microbial communities can impact the resulting chemistry and mass loss of litter (Wickings et al, 2012;Allison et al, 2013), particularly if the litter is of similar composition to that which is frequently experienced by the microbes (Ayres et al, 2009;Freschet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Soil disturbance across a wide range of systems can have rapid and persistent impacts on soil microbial communities [106], and our study is the first to evaluate soil fungal responses to tropical logging and oil palm agriculture using molecular techniques. Some of the differences in the soil physicochemical properties across land-use types may explain the variation in fungal composition we observed, although further experimentation will be necessary to identify causal links.…”
Section: Discussionmentioning
confidence: 99%